The aim of this paper is to analyze, in its diachronic development, the reality of the ethnic and social differentiation in Cyrenaica between battiad age and ptolemaic domination, and the way in which it is reflected on the territory, both of the cities and of the surrounding chōra. Central to this discussion is the presence of indigenous element and its relationship, variously articulated and influenced by multiple factors, with Greek colonists. From a review of literary and epigraphic sources, though lacking in details and clarifications, we try to clarify the meaning and the juridical significance of a terminology that refers to the articulation of a society divided between different ethnic groups but also between Greek citizens with different enjoyment of rights, as the inexhaustible testimony of the ptolemaic diagramma seems to let it suppose (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2018)
Nel presente contributo si vuole analizzare, nel suo sviluppo diacronico, la realtà delle differenziazioni etniche e sociali in Cirenaica fra l’epoca battiade e la dominazione lagide e il modo in cui queste vengono a riflettersi sul territorio, sia delle città che della chōra circostante.Centrale in questa disamina è la presenza dell’elemento indigeno e il suo rapportarsi, variamente articolato e condizionato da molteplici fattori, con i coloni greci.Da un riesame della documentazione letteraria ed epigrafica, pur avara di dettagli e precisazioni, si cerca di chiarire il significato e la valenza giuridica di una terminologia che fa riferimento all’articolazione di una società divisa fra gruppi etnici diversi ma anche fra cittadini greci con differente fruizione dei diritti, come la testimonianza inesauribile del diagramma tolemaico sembra lasciar trasparire